Long March Toward Safe and Effective Analgesia by Enhancing Gene Expression of Kcc2: First Steps Taken - Liedtke, Wolfgang (Frontiers in Molecular Neuroscience, 2022)
Low intraneuronal chloride in spinal cord dorsal horn pain relay neurons is critical for physiologic transmission of primary pain afferents because low intraneuronal chloride dictates whether GABA-ergic and glycin-ergic neurotransmission is inhibitory. If the neuronal chloride elevates to pathologic levels, then spinal cord primary pain relay becomes leaky and exhibits the behavioral hallmarks of pathologic pain, namely hypersensitivity and allodynia. Low chloride in spinal cord dorsal horn neurons is maintained by proper gene expression of Kcc2 and sustained physiologic function of the KCC2 chloride extruding electroneutral transporter. Peripheral nerve injury and other forms of neural injury evoke greatly diminished Kcc2 gene expression and subsequent corruption of inhibitory neurotransmission in the spinal cord dorsal horn, thus causing derailment of the gate function for pain. Here I review key discoveries that have helped us understand these fundamentals, and focus on recent insights relating to the discovery of Kcc2 gene expression enhancing compounds via compound screens in neurons. One such study characterized the kinase inhibitor, kenpaullone, more in-depth, revealing its function as a robust and long-lasting analgesic in preclinical models of nerve injury and cancer bone pain, also elucidating its mechanism of action via GSK3β inhibition, diminishing delta-catenin phosphorylation, and facilitating its nuclear transfer and subsequent enhancement of Kcc2 gene expression by de-repressing Kaiso epigenetic transcriptional regulator. Future directions re Kcc2 gene expression enhancement are discussed, namely combination with other analgesics and analgesic methods, such as spinal cord stimulation and electroacupuncture, gene therapy, and leveraging Kcc2 gene expression-enhancing nanomaterials.